Between Situational Leadership and Employee Motivation on Individual Performance in Indonesian Manufacturing Industry - Hanasi, Raihan A. (Yayasan Sinergi Kawula Muda, 2023)
This study looks into how employee motivation and situational leadership affect individual performance in the manufacturing sector in Indonesia. Survey methods were used quantitatively to gather data from employees at different organizational levels. The study employed Structural Equation Modeling (SEM) in conjunction with Partial Least Squares (PLS) analysis to examine the connections among situational leadership, worker motivation, and individual performance. The findings show that individual performance and employee motivation are both positively impacted by situational leadership. It was also shown that the relationship between situational leadership and individual performance is mediated by employee motivation. Moreover, it was shown that job design and organizational culture were important moderators that increased the effect of situational leadership on worker motivation and the ensuing performance outcomes. These results highlight how crucial motivational work environments and adaptive leadership techniques are for enhancing individual performance in the setting of Indonesian manufacturing.